2017
DOI: 10.1002/adma.201701733
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymer for Voltage‐Controlled Release of Molecules

Abstract: Conjugated polymers are attractive in numerous biological applications because they are flexible, biocompatible, cost‐effective, solution‐processable, and electronic/ionic conductive. One interesting application is for controllable drug release, and this has been realized previously using organic electronic ion pumps. However, organic electronic ion pumps show high operating voltages and limited transportation efficiency. Here, the first report of low‐voltage‐controlled molecular release with a novel organic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
(87 reference statements)
2
37
0
Order By: Relevance
“…At this point, the surface energy of P3HT layer is altered due to combination of SO24 and holes and the surface wettability of P3HT film change from hydrophobicity to hydrophilicity. After turning off the switch for 15 min, the SO24 diffuses back to Na 2 SO 4 aqueous solution and contact angle of deionized water returns to about 93.7°, which is a chemical reduction process, as shown in Figure 3b 13…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At this point, the surface energy of P3HT layer is altered due to combination of SO24 and holes and the surface wettability of P3HT film change from hydrophobicity to hydrophilicity. After turning off the switch for 15 min, the SO24 diffuses back to Na 2 SO 4 aqueous solution and contact angle of deionized water returns to about 93.7°, which is a chemical reduction process, as shown in Figure 3b 13…”
Section: Resultsmentioning
confidence: 99%
“…The release behavior of small molecules of FDRD can be tuned by change wettability of P3HT. Many research works have reported that the wettability of P3HT can be regulated by a bias voltage 9,13. The contact angle variation of water with a bias voltage applied between Ag/AgCl electrode in Na 2 SO 4 aqueous solution and bottom electrode is shown in Figure a (Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations